The Value of caring : the story of Eleonor Roosevelt - Johnson, Spencer (La Jolla, CA : Value Comm., Inc Pub, 1997)
A biography of the First Lady who not only aided her husband after he was stricken with polio but also served as a delegate to the United Nations where she helped start UNICEF.
Keywords: Roosevelt, Eleonor, 1884-1962; Presidents' Wines--United States--Biography; First Ladies; Kindness